2013
DOI: 10.4047/jap.2013.5.4.471
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of Co-Cr dental alloy: effects on nanostructure and Rockwell hardness

Abstract: PURPOSEThe aim of the study was to evaluate the effect of annealing on the nanostructure and hardness of Co-Cr metal ceramic samples that were fabricated with a direct metal laser sintering (DMLS) technique.MATERIALS AND METHODSFive groups of Co-Cr dental alloy samples were manufactured in a rectangular form measuring 4 × 2 × 2 mm. Samples fabricated by a conventional casting technique (Group I) and prefabricated milling blanks (Group II) were examined as conventional technique groups. The DMLS samples were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 30 publications
0
41
1
Order By: Relevance
“…Oyague et al and Kim et al separately evaluated the fit of dental prostheses produced by SLM and reached different conclusions about the suitability of SLM technology in producing dental prostheses . In terms of hardness, elastic modulus and strength, Ayyildiz et al concluded that CoCr produced by laser AM is suitable for dental applications …”
Section: Additive Manufactured Materials For Orthopaedic Implantsmentioning
confidence: 95%
“…Oyague et al and Kim et al separately evaluated the fit of dental prostheses produced by SLM and reached different conclusions about the suitability of SLM technology in producing dental prostheses . In terms of hardness, elastic modulus and strength, Ayyildiz et al concluded that CoCr produced by laser AM is suitable for dental applications …”
Section: Additive Manufactured Materials For Orthopaedic Implantsmentioning
confidence: 95%
“…Among the bio-active functions proposed for dental materials, antibacterial activity seems the most promising [17,29]. The use of CoCr based alloys has become popular in recent years as a coping material for use in restorative dentistry [6,7]. As a widely used coping material, CoCr based alloy is bio-inert which does not possess inherent antibacterial properties, and therefore is easily colonized by bacteria with subsequent development of a biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, CoCr based alloys are widely used in prosthodontics due to a combination of favorable properties, including mechanical strength, ductility, corrosion resistance and biocompatibility, which makes them broadly applicable in a variety of applications with fixed and removable restorations. CoCr based alloys, based on SLM technology, were recently introduced for manufacturing base metal coping [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The authors' findings for phase transformation status and microstructural characterization of the samples that were manufactured by the DMLS technique provide novel data for academics in this field. However, there are some important points I would like to add, as we previously published a DMLS study in another journal [2].…”
Section: Dear Editormentioning
confidence: 99%
“…However, this technique is still very new for many clinicians manufacturing Co-Cr metal ceramic substructures, and therefore, the steps of the procedure and the factors that affect product quality are not well known. In our paper, we aimed to present the micromechanical properties of Co-Cr samples that were manufactured by the DMLS technique and the importance of the laboratory procedures for biological and mechanical factors [2]. As we outlined in our study, the annealing process is an inevitable step for the clinical use of these products.…”
Section: Dear Editormentioning
confidence: 99%